ANALISIS HCI (HUMAN COMPUTER INTERACTION) PADA SISTEM INFORMASI AKADEMIK UNIVERSITAS NEGERI MAKASSAR UNTUK PENGUKURAN USER EXPERIENCE - Tri Agung Nusantara; Husain Syam; Yunus Tjandi (UNM Journal of Technology and Vocational, 2023)
This study aims to determine: (1) Perceived ease of use; (2) Facilitating Conditions; and (3) Perceived Usefulness in State University of Makassar Information System. Mixed method approach used in this study. The population in this study were student of the Class of 2019 at State University of Makassar. The sample of this study amounted to 387 students spread across 9 faculties where the sampling technique used simple random sampling. Research data were collected using questionnaires and interviews. Data obtained from this study were analyzed using descriptive statistics. The result of this study indicate: (1) perceived ease of use is good category, (2) Facilitating Conditions is good category, and (3) Perceived Usefulness is good category. So that overall the UNM Academic Information System is good and only requires some training to users for the use of the features in the UNM Academic Information System.